Pengaruh pembiayaan bagi hasil, non Performing Financing (NPF) dan Biaya Operasional Pendapatan Operasional (BOPO) terhadap Return On Assets (ROA) pada bank umum syariah - Nur Kholis; Lintang Kurniawati (Faculty of Economics, Universitas Islam Indonesia, 2018)
This study aims to analyse the effect of profit-sharing financing, Non-Performing Financing (NPF) and Operating Expense Ratio (OER) both simultaneously and partially on ROA (Return On Assets) of Islamic banks in Indonesia. Sampling technique used in this study is random sampling. Data analysis used in this study is multiple linear regression with SPSS 21 for Windows. The result shows that partially profit-sharing financing and OER have no effect toward ROA of Islamic banks, but NPF has an effect.